The Periodic Table Elements with Style - Dingle, Adrian (New York Kingfisher, 2007)
Web-style "homepages" introduce to budding chemists each of the chemical elements from the periodic table, complete with witty and informative profiles written by the elements themselves.
Hydrogen -- Alkali metals -- Alkaline earth metals -- Transition elements -- Boron elements -- Carbon elements -- Nitrogen elements -- Oxygen elements -- Halogen elements -- Noble gases -- Lanthanides and actinides -- Transactinides -- Index -- Glossary.
Keywords: Periodic Law- Tables-Juvenile literature; Chemical Elements-Juvenile literature